Use of fecal and serum estradiol analysis for estimation of pregnancy status in the mare - Eddy, Kathleen M., author; Nett, Terry M., advisor; Eckery, Douglas C., advisor; Baker, Dan L., committee member; Bruemmer, Jason E., committee member; Hollinshead, Fiona K., committee member (Colorado State University. Libraries, 2020)
Overabundant feral horse populations within the United States cause significant and detrimental economic and ecological impacts. Aside from helicopter roundups and long-term holding facilities, current management practices of feral horses include application of contraception in conjunction with non-invasive determination of pregnancy through the measurement of fecal steroid metabolite monitoring. Prior to this study, the earliest timing of definitive pregnancy diagnosis was between 120 – 180 days of gestation, when measuring total unconjugated fecal estrogens (Bamberg et al 1984; Kirkpatrick et al 1989), or from samples taken at least 150 days of gestation when measuring fecal estrone sulfate (Henderson et al 1998 and 1999). The studies in this thesis examined measurement of estradiol 17β, an estrogen that has yet to be quantified in the feces of domestic and feral mares. The overall objectives of the studies in this thesis were to determine the efficacy of fecal and serum estradiol measurement in the estimation of pregnancy in the mare, as well as the definitive timing within gestation when fecal and serum concentrations diverged from those of non-pregnant mares. The first study of this thesis utilized 8 pregnant domestic mares with known embryo transfer dates, as well as 8 non-pregnant cycling mares. Weekly fecal and blood samples were collected from the pregnant mares for the entirety of gestation, while daily fecal and blood samples were taken from the cycling mares for 23 days. Radioimmunoassay (RIA) specific for estradiol 17β was used to quantify extracted fecal and serum samples for the two groups. It was found that at a mean of 105 days of gestation, fecal estradiol concentrations in pregnant mares surpassed non-pregnant mare concentrations, with a calculated cut-off value of 10 pg/mg feces. Serum estradiol concentrations of pregnant mares surpassed those of non-pregnant mares at an average of 128 days of gestation, with a concentration of at least 46 pg/mL serum. Additionally, aside from increasing earlier in gestation, compared to serum, fecal estradiol was found to fluctuate less throughout pregnancy. The second study of this thesis examined 77 fecal and serum samples collected from 51 feral mares during two roundups in Theodore Roosevelt National Park (THRO), as well as 272 individual fecal samples collected over a 6 year period from the same 51 mares. Using the cut-off days and concentrations affiliated with the first study, correlative comparisons were made for the feral mare samples, and pregnancy status was elucidated. Of the 62 fecal samples taken during the roundups past the cut-off day of 105 days, 60 of them surpassed the fecal cut-off concentration of 10 pg/mg feces. Thirty-four of 49 serum samples taken past the cut-off day of 128 surpassed the cut-off concentration of 46 pg/mL. While only two of the 62 fecal samples taken past the cut-off of 105 days were below the cut-off concentration, 14 of the 49 serum samples taken past cut-off day 128 were below the serum cut-off concentration of 46 pg/mL serum. This trend was similar to what was seen in domestic mares. Although the majority of the field fecal samples were collected in November, there were also the fecal samples from the September and October roundups, as well as a few February samples. While all but 4/131 samples from November were in the estimated 152 -202 day range of gestation, 6/41 in September, and 9/36 in October were below cut-off day 105. In a population similar to THRO, this could potentially result in 14.6% and 25% of concentrations from samples taken in September and October being too low to differentiate between pregnant and non-pregnant individuals. However, when examining the estimated sample distribution range of 101-151 days, 96% of September samples, 91.7% of both October and November samples resulted in concentrations above the cut-off value of 10 pg/mg. From the studies completed in both domestic and feral mares, it can be said with confidence that the quantification of estradiol 17β using RIA is a reliable method for indicating pregnancy status in the mare. Mares with fecal estradiol concentrations above 10 pg/mg from samples taken at least 105 days post conception were pregnant, as were mares with measured serum estradiol concentrations above 46 pg/mL collected after 128 days post conception. Additionally, fecal samples taken from feral mares during the non-breeding season in THRO resulted in 96% of samples collected in September, and 91.7% of samples collected in October and November resulting in concentrations above the cut-off concentration of 10 pg/mg feces. This data supports the reliability of fecal estradiol measurement as a tool for pregnancy status determination in the mare.
Keywords: feces; serum; mare; estradiol